Beyond BOLD: Optimizing functional imaging in stroke populations. Issue 4 (2nd December 2014) - Veldsman, Michele; Cumming, Toby; Brodtmann, Amy
Abstract: Blood oxygenation level‐dependent (BOLD) signal changes are often assumed to directly reflect neural activity changes. Yet the real relationship is indirect, reliant on numerous assumptions, and subject to several sources of noise. Deviations from the core assumptions of BOLD contrast functional magnetic resonance imaging (fMRI), and their implications, have been well characterized in healthy populations, but are frequently neglected in stroke populations. In addition to conspicuous local structural and vascular changes after stroke, there are many less obvious challenges in the imaging of stroke populations. Perilesional ischemic changes, remodeling in regions distant to lesion sites, and diffuse perfusion changes all complicate interpretation of BOLD signal changes in standard fMRI protocols. Most stroke patients are also older than the young populations on which assumptions of neurovascular coupling and the typical analysis pipelines are based. We present a review of the evidence to show that the basic assumption of neurovascular coupling on which BOLD‐fMRI relies does not capture the complex changes arising from stroke, both pathological and recovery related. As a result, estimating neural activity using the canonical hemodynamic response function is inappropriate in a number of contexts. We review methods designed to better estimate neural activity in stroke populations. One promising alternative to event‐related fMRI is a resting‐state‐derived functional connectivity approach. Resting‐state fMRI is well suited to stroke populations because it makes no performance demands on patients and is capable of revealing network‐based pathology beyond the lesion site. Hum Brain Mapp 36:1620–1636, 2015 . ©2014 Wiley Periodicals, Inc .